Two-photon NAD(P)H-FLIM reveals unperturbed energy metabolism of Ascaris suum larvae, in contrast to host macrophages upon artemisinin derivatives exposure - Zaneta D. Musimbi; Arkadi Kundik; Jürgen Krücken; Anja E. Hauser; Sebastian Rausch; Peter H. Seeberger; Raluca Niesner; Ruth Leben; Susanne Hartmann (Scientific Reports)
Abstract Soil-transmitted helminths (STH) are widespread, with Ascaris lumbricoides infecting millions globally. Malaria and STH co-infections are common in co-endemic regions. Artemisinin derivatives (ARTs)—artesunate, artemether, and dihydroartemisinin—are standard malaria treatments and are also known to influence the energy metabolism of parasites, tumors, and immune cells. Herein, we explore the potential of ARTs to influence ascariasis either by directly targeting larvae or indirectly by modifying macrophage responses. Ascaris suum third-stage larvae and porcine IL-4 polarized (M2-like) macrophages were exposed to ARTs in vitro, and their metabolism was evaluated using two-photon NAD(P)H-FLIM. Both larvae and M2-like macrophages exhibited a steady-state bioenergetic profile of high oxidative phosphorylation and low anaerobic glycolysis. In A. suum larvae, two metabolically distinct regions were identified, with particularly high DUOX activity in the pharynx compared to the midgut; however, ARTs did not alter these profiles. In contrast, exposure of M2-like macrophages to ARTs induced a metabolic shift towards high anaerobic glycolysis and reduced metabolic activity, suggesting a possible indirect effect of ARTs on the helminth infection. Overall, two-photon NAD(P)H-FLIM proved to be a powerful tool for studying specific metabolic pathways in Ascaris larvae and host macrophages, offering valuable insights into the metabolic mechanisms of drug action on both parasite and host.